Determining the Levels of Contamination of Locally Compounded Poultry Feeds and Ingredients by Fungi of the Genus Penicillium and Aspergillus within Three Agro-Ecological Zones of Nigeria - Akinmusire, Olubamise Oyekemi; Omomowo Israel Olawale; Divine-Anthony Ofon-mbuk (Newest Updates in Agriculture and Veterinary Science Vol. 1, 2022)
This research sought to determine the levels of contamination by various species of Aspergillus and Penicillium contaminating poultry feeds and feed ingredients in three agro-ecological zones of Nigeria. The presence of fungi in feed sometimes leads to low consumption or total rejection of feeds by poultry birds. A total of 52 samples of feed (n=13) and feed ingredients (n=39) were collected across 3 agro-ecological zones (involving 6 states) of Nigeria. The pour plate technique was applied to isolate various mycological media. Utilizing macroscopic and microscopic traits, the identity of isolates of Aspergilli and Penicilli was determined. The feed samples were completely contaminated with Aspergillus species, while 63% were polluted with Penicillium species. In the feed and feed additives, nine Aspergillus species and five Penicillium species were found. The highest occurring fungal genus was Aspergillus, specifically, Aspergillus niger and Aspergillus flavus species were the highest occurring species. The most common Penicillium species identified from compounded poultry feed and feed ingredient samples was Penicillium glabrum. A number of Aspergillus and Penicillium species were present in all of the feed samples (100%) in various amounts. All of the feed items were contaminated, except for the samples of bone meal, which were contaminated by 78%.